CFD modeling and validation of a dynamic slab heating process in an industrial walking beam reheating furnace. (5th March 2018) - Tang, Guangwu; Wu, Bin; Bai, Dengqi; Wang, Yufeng; Bodnar, Rick; Zhou, Chenn
Highlights: A comprehensive CFD model has been developed for a walking beam reheating furnace. Industrial experiment was conducted under the typical operating condition. The CFD model has been validated with industrial experimental data. The validated CFD model using dynamics mesh model to predict the real slab dynamic reheating process. Abstract: Comprehensive numerical modeling and validation on an industrial walking beam slab reheating furnace were conducted. A transient three-dimensional Computational Fluid Dynamics (CFD) model was developed to simulate the flow characteristics, combustion process and multi-scale heat transfer inside the reheating furnace. The actual geometry of the furnace was used and typical operating conditions were simulated. Specific walking speeds of slabs in production were modeled using a dynamic mesh model which is controlled by a user defined function (UDF) solved using ANSYS Fluent. Fuel variations at different zones with time were also considered. The model was validated with instrumented slab trials conducted at the SSAB Mobile mill. The temperature field in the furnace and the temperature evolution of a slab predicted by the CFD model are in good agreement with those obtained from the instrumented slab trials. Based on the simulation results, the slab reheating process and the temperature uniformity of a slab at discharge were able to be properly evaluated.